Productivity and growing-season stability in common bean (Phaseolus vulgaris L.) under contrasting ecogeographic conditions - L. Yu. Novikova; A. A. Berzegova; M. V. Gurkina; T. V. Buravtseva (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the effect size of the environment versus breeding-oriented plant traits is relevant under climate change. Identification of stable accessions while evaluating the source material in contrasting environments can increase the efficiency of breeding practice.Materials and methods. Thirty common bean accessions from the VIR collection were sown for 3 years in the contrasting environments of Maikop and Astrakhan. Eight useful agronomic traits were studied according to VIR’s guidelines. Statistical processing was carried out using ANOVA, correlation and regression analyses. Environmental stability of productivity was assessed according S. A. Eberhart and W. A. Russell (1966).Results and discussion. The study of the variability of traits showed the stability of the sowing-to-ripening period duration (average coefficient of variation: 10.9%) and 1000 seed weight (17.3%). The effect of the genotype was the determining factor only for 1000 seed weight (67.6% of the variance). The growing season duration, number of pods per plant, number of seeds per pod, and productivity depended more on the environments. Productivity formation patterns were basically the same at both sites: productivity of an accession depended on the number of pods, and 1000 seed weight was negatively related to the number of seeds per pod. The growing season in Maikop depended on the flowering-to-ripening period (r = 0.73); in Astrakhan, on the sprouting-to-flowering period (r = 0.85). The duration of the sowing-to-sprouting and sprouting-to-flowering periods significantly correlated with mean temperatures (r = –0.87 and 0.87, respectively), while the flowering-to-ripening period did not depend on the mean temperature.Conclusion. Accessions relatively stable in their productivity and duration of the growing season were identified. They demonstrated both determinant and indeterminate growth, attesting to the prospects of breeding work with different common bean groups.